Compromised Photosynthetic Electron Flow and H2O2 Generation Correlate with Genotype-Specific Stomatal Dysfunctions during Resistance against Powdery Mildew in Oats - Sánchez-Martín, Javier; Montilla-Bascón, Gracia; Mur, Luis A. J.; Rubiales, Diego; Prats, Elena (Frontiers in Plant Science, 2016)
Stomatal dysfunction known as “locking” has been linked to the elicitation of a hypersensitive response (HR) following attack of fungal pathogens in cereals. We here assess how spatial and temporal patterns of different resistance mechanisms, such as HR and penetration resistance influence stomatal and photosynthetic parameters in oat (Avena sativa) and the possible involvement of hydrogen peroxide (H2O2) in the dysfunctions observed. Four oat cultivars with differential resistance responses (i.e., penetration resistance, early and late HR) to powdery mildew (Blumeria graminis f. sp. avenae, Bga) were used. Results demonstrated that stomatal dysfunctions were genotype but not response-type dependent since genotypes with similar resistance responses when assessed histologically showed very different locking patterns. Maximum quantum yield (Fv/Fm) of photosystem II were compromised in most Bga–oat interactions and photoinhibition increased. However, the extent of the photosynthetic alterations was not directly related to the extent of HR. H2O2 generation is triggered during the execution of resistance responses and can influence stomatal function. Artificially increasing H2O2 by exposing plants to increased light intensity further reduced Fv/Fm ratios and augmented the patterns of stomatal dysfunctions previously observed. The latter results suggest that the observed dysfunctions and hence a cost of resistance may be linked with oxidative stress occurring during defense induced photosynthetic disruption.